Factors predicting inmates’ adaptation to imprisonment in Lithuania - Mikalauskienė, Viktorija; Laurinavičius, Alfredas (Psichologija, 2019)
Adaptation to imprisonment in a correctional facility is a convicted person’s psychological and behavioural response to the environment of a correctional facility and the imprisonment situation (Fedock, 2017). Convicted persons who have successfully adapted to the new environment are able to satisfy their basic needs, do not come into conflicts with the correctional facility administration or other inmates, and do not experience strong negative emotions, among other things. There seems to be a relationship between maladaptation to a correctional facility and a lower motivation to modify one’s criminal behaviour as well as recidivism (Loper, 2002; Zamble & Porporino, 1988). While inmates’ adaptation to imprisonment in correctional facilities and factors predicting this adaptation have received significant attention from foreign researchers over the last several decades, it still remains an under-researched field in Lithuania. The purpose of this study is to identify the factors that predict convicted persons’ adaptation to imprisonment in Lithuanian correctional facilities. The study sample included male inmates (N = 331) aged 18 to 68 (M = 35,17, SD = 10,75) from five correctional facilities in Lithuania. Adaptation was evaluated using the Prison Problem Scale (Zamble & Porporino, 1988), Beck Depression Inventory-II (Beck, Steer, & Brown, 1996) and Beck Anxiety Inventory (Beck, Epstein, Brown, & Steer, 1988). Factors related to adaptation were assessed using the Criminal Sentiments Scale – Modified (CSS-M, Simourd, 1997) and the demographic information questionnaire. Poorer adaptation to a correctional facility was observed among those study participants who were underage, when they faced a conviction for the first time, who had been unemployed or used drugs before incarceration as well as those who haven’t remained in contact with their romantic partner or friends during imprisonment. Poorer adaptation to a correctional facility also correlated with more pronounced criminal attitudes. The study found that the factors that best predicted adaptation was criminal attitudes and staying in touch with friends or a romantic partner. The factors explained up to 16% of the variance of variables used to assess adaptation.
Keywords: inmate; adaptation; correctional institution